Modified Particle Swarm Optimization Based Harmonic Minimization in Hybrid Cascaded Multilevel Inverter - Routray A.; Singh R.K.; Mahanty R. (My University, 2025)
Harmonic minimization in multilevel inverters is a complex optimization problem that involves non-linear transcendental equations. Selective harmonic elimination pulse width modulation (SHE-PWM) is a widely used switching technique of cascaded multilevel inverters which eliminates low-order harmonics from output voltage waveform. The equations involved for this technique are transcendental. Evolutionary computational technique is used to for solving requirements of such problems. In this paper, a modified particle swarm optimization (MPSO) technique is used for the SHE-PWM technique. MPSO has been used to compute all the switching angles of the proposed eleven level HC-MLI for eliminating specified odd harmonics (5 th , 7 th ) from the output voltage. It also improves the convergence rate in global and local search. The obtained results are compared with convergence rate of other algorithms, local optima and finding better fitness of individuals. The experimental prototype of an eleven-level hybrid cascaded H-bridge multilevel inverter (HC-MLI) has been developed in laboratory to verify the effectiveness of the proposed work. © 2018 IEEE.